Kajian Daya Dukung Fungsi Lindung dan Lahan Berbasis Spasial di Kabupaten Sumbawa - Alfian Pujian Hadi; Dewi Putri Lestari; Nurin Rochayati; Mas’ad Mas’ad; Firman Ali Rahman (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This study aims to determine the carrying capacity of the protected function and the carrying capacity of land based on the ratio of land availability and demand for land in Sumbawa Regency. The research method uses a quantitative descriptive approach with an analysis of the carrying capacity of the protected function and the analysis of the carrying capacity of the land is carried out using an approach to land availability and land requirements. The results showed that the carrying capacity of the protected function of 24 sub-districts in Sumbawa Regency obtained 4 sub-districts (16.7%) in very good category, 6 sub-districts (25%) in good category, 2 sub-districts (8.3%) in moderate category, 3 sub-districts ( 12.5%) in the damaged category, and 9 sub-districts (37.5%) in the very damaged category. The sub-districts that fall into the category of severely damaged environmental carrying capacity include: Labuhan Badas, North Moyo, Moyo Hulu, Ropang, Lape, Lopok, Labangka, Maronge, and Tarano sub-districts with an environmental carrying capacity value below 0.20. The sub-districts in Sumbawa Regency that have a deficit land carrying capacity status (25%), include: Alas, Utan, Buer, Rhee, Batulanteh, Sumbawa, and Unterwilis sub-districts. Judging from the ratio of land availability and land demand, it is known that Alas, Sumbawa, and Labuhan Badas sub-districts have the smallest ratio, meaning that the level of land demand in the three sub-districts is high compared to land availability, so that the existing land is no longer able to support the needs of the population.